Semelhança de triângulos: um estudo propositivo atráves do Scratch - Horbach, Ivan Carlos (2020)
The expression “Computational Thinking” was introduced by Jeannete Wing in 2006 asa skill that involves problem-solving, understanding human behavior and abstraction ofideas. One of the ways of approaching “Computational Thinking” in Basic Educationis the use of software to the introduce programming, such as Scratch. Therefore,with theoretical basis in Ausubel’s Meaningful Learning and in the ideas of Papert’sConstructionism, this work presents the results of the elaboration and application of adidactic sequence, which used Scratch as a tool for learning the similarity content oftriangles. The case study, with a duration of 20 hours in class, occurred with studentsfrom the 9thgrade of Basic Education in a public school. This data was collected byquestionnaires, before and after applying the didactic sequence and the elaboration ofa final project by the participants. The analysis of the results was realized by qualitativeway, highlighting the meaningful learning, according to Ausubel, of the content similarityof triangles.